2012
DOI: 10.1371/journal.pone.0037499
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Change in Non-Arteritic Anterior Ischemic Optic Neuropathy and Its Influence on Visual Outcome

Abstract: PurposeTo evaluate changes in cup/disc (C/D) diameter ratios and parapapillary atrophy in patients with non-arteritic anterior ischemic optic neuropathy (NA-AION), using morphometric methods.MethodsThe clinical non-interventional study included 157 patients with unilateral or bilateral NA-AION. Optic disc photographs taken from both eyes at the end of follow-up were morphometrically examined.ResultsFollow-up was 86.3±70.3 months. Horizontal and vertical disc diameters (P = 0.30;P = 0.61, respectively), horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Recently, Jonas et al 18 reported that NAION did not affect parapapillary atrophy. However, to the best of our knowledge, deeper ONH structures have not been studied in patients with NAION.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jonas et al 18 reported that NAION did not affect parapapillary atrophy. However, to the best of our knowledge, deeper ONH structures have not been studied in patients with NAION.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that diff erence in the structure of extracellular matrix infl uences the stability of laminar region. Vascular supply of ONH in the eyes with POAG passes vertically (60% of cases) through temporal part of the papilla and is more sensitive to ischemia when the perfusion pressure decreases 26,27 . In the eyes with NAION, segmental excesses probably occur due to anatomic division of the microvasculature supplying the ONH into distinct upper and lower halves.…”
Section: Discussionmentioning
confidence: 99%
“…If the visual acuity did not allow evaluation with Humphrey perimetry, patients underwent Goldmann perimetry (I-2e, I-4e and IV-4e targets). The optic disc photographs of both eyes of the patients in this study were digitised, and the horizontal and vertical optic disc diameters were measured 22 23…”
Section: Methodsmentioning
confidence: 99%